Mujeres y educación: Representación desde la prensa antioqueña en la década de 1920 - Urrego, Paula Andrea (Revista Ciencias y Humanidades, 2025)
This research presents and analyses the representation of women in the Antioquia’s journals during the twenties decade. This period was a conjunctural epoch for the women’s rights. For this analysis, it was taken as a reference the ideological position of newspapers and magazines in order to compare the differences or similarities in the ideas and positions of the newspapers about education. The analyzed positions were divided into: those related to traditional education and those concerning modern education. These were a reflection of the several changes in the political views in the country in that decade, and the difficulties of the conservative population for accepting the new roles that women can play in a modern society. Este artículo analizó las representaciones de las mujeres en la prensa antioqueña en la década de 1920. Este periodo fungió como una coyuntura para la movilización de éstas por sus derechos. Para el análisis se tomó como referencia la posición ideológica de los periódicos y revistas con el ánimo de comparar las diferencias o similitudes en sus discursos acerca de la educación. Al hacer la revisión se encontró una dicotomía entre la defensa de la educación moral y la educación moderna o intelectual. Esto fue un reflejo de los cambios que se estaba dando en el país y la dificultad de la sociedad conservadora para aceptar las mejoras en las condiciones de las mujeres.